Software testing process for shared banking services (SBS) system - Arbain @ Sulaiman, Norakmar (2009)
Software testing is one of the main activities in software development life cycle. This process consists of a few activities, which includes developing test plan and strategy, test design, test execution and evaluation of test result. However, a customized testing process is required for a specific domain in order to ensure the correctness and completeness of the test result. This project proposed a customized testing process for Shared Banking Services (SBS) system, which developed by R@PIC, HeiTech. Study was conducted in order to identify the specific modules in SBS and its characteristics which differentiate it from other software applications. Besides that, three testing methodologies, which are HeiTech Testing Process, RUP Test Discipline and Systematic Test and Evaluation Process (STEP), were compared based on criteria such as main activities, roles and responsibilities, artifacts and level of testing. The comparison result was then map to the characteristic of SBS to produce the proposed software testing process for SBS.